Numerical simulation of pounding damage to bridge structures under spatially varying ground motions - Bi, Kaiming; Hao, Hong (Pergamon, 2013)
Previous studies of pounding responses of bridge structures to seismic loadings are usually based on the point to point pounding assumption by using the simplified lumped mass model or beam-column element model. It has been found these simplified models can be used to calculate bridge pounding response with consideration of only the longitudinal excitation. In a real bridge structure under seismic loading, pounding could take place along the entire or part of surfaces of the adjacent segments. Moreover, torsional response of the adjacent decks owing to the asymmetric deck or induced by spatially varying transverse ground motions at multiple bridge supports may result in eccentric poundings between adjacent bridge decks. A detailed 3D finite element model is necessary to consider the surface to surface and torsional response induced eccentric poundings and the corresponding damage. This paper performs numerical simulations of pounding damage between bridge girders and between bridge girder and the corresponding abutment of a two-span simply-supported bridge to spatially varying ground motions based on a detailed 3D finite element model by using the explicit finite element code LS-DYNA. The dislocation and unseating potentials of the bridge are also modelled. The bridge components including the bridge girders, abutments, pier, bearings, longitudinal reinforcement bars and stirrups are included in the model. The non-linear material behaviour including the strain rate effects of concrete and steel rebar are considered. The spatially varying ground motions are stochastically simulated. The damage mechanism of the bridge under spatially varying seismic loadings is examined. Numerical results show that the method adopted in the present paper can realistically capture the seismic induced damage of bridge structures.